Anode for all-solid secondary batteries, manufacturing method thereof and all-solid secondary battery
By coating carbon materials in all-solid-state secondary batteries with a lithium ion conductive oxide layer and using a sulfide-based electrolyte, the electrode resistance is reduced, enhancing charging capacity and load characteristics.
Patent Information
- Application Number
- JP2024198664
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-05-28
AI Technical Summary
Existing all-solid-state secondary batteries face challenges in achieving low resistance values and high charging capacity during constant-current charging, particularly when using carbon materials as negative electrode active materials due to poor interface formation with sulfide-based solid electrolytes.
A negative electrode for all-solid-state secondary batteries is developed with a carbon material surface coated with a lithium ion conductive oxide layer, utilizing a sulfide-based solid electrolyte, ensuring a high affinity and effective interface, thereby reducing resistance and enhancing lithium ion acceptance.
The solution results in a negative electrode with lower resistance and improved load characteristics, increasing the charging capacity during constant-current charging (CC capacity) and overall performance of the all-solid-state secondary battery.
Smart Images

Figure 2025013702000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode for an all-solid-state secondary battery having a low resistance value, a method for producing the same, and an all-solid-state secondary battery using the negative electrode. [Background technology]
[0002] In recent years, with the development of portable electronic devices such as mobile phones and notebook personal computers, and the practical application of electric vehicles, there has been a demand for small, lightweight secondary batteries with high capacity and high energy density.
[0003] Currently, lithium secondary batteries, particularly lithium ion secondary batteries, that can meet this demand use lithium-containing composite oxides such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2) as the positive electrode active material, graphite or the like as the negative electrode active material, and an organic electrolyte solution containing an organic solvent and a lithium salt as the non-aqueous electrolyte.
[0004] Furthermore, with the further development of devices that use lithium-ion secondary batteries, there is a demand for lithium-ion secondary batteries with longer life, higher capacity, and higher energy density.
[0005] For example, with regard to increasing the capacity of a lithium ion secondary battery having an organic electrolyte (nonaqueous electrolyte secondary battery), Patent Document 1 proposes a technology in which the surface of a carbon material, which is a negative electrode active material, is coated with a solid electrolyte having lithium ion conductivity in order to reduce the irreversible capacity of the negative electrode.
[0006] Furthermore, in lithium-ion secondary batteries, there is a demand for improved reliability as well as longer life, higher capacity, and higher energy density.
[0007] However, since the organic electrolyte used in the lithium ion secondary battery contains an organic solvent, which is a flammable substance, the organic electrolyte may generate abnormal heat when an abnormality such as a short circuit occurs in the battery. In addition, with the recent trend toward higher energy density of lithium ion secondary batteries and an increasing amount of organic solvent in the organic electrolyte, there is a demand for even higher reliability of lithium ion secondary batteries.
[0008] In the above circumstances, all-solid-state lithium secondary batteries that do not use organic solvents (all-solid-state secondary batteries) are attracting attention. All-solid-state secondary batteries use a molded body of a solid electrolyte that does not use an organic solvent instead of the conventional organic solvent-based electrolyte, and are highly safe without the risk of abnormal heat generation of the solid electrolyte.
[0009] In addition, various improvements have been attempted for all-solid-state secondary batteries. For example, Patent Document 2 proposes that structural defects of a negative electrode active material having a graphite structure are covered with particulate lithium niobate having an average particle size of 1.5 nm or less, thereby suppressing heat generation and reducing resistance, and using the coated negative electrode active material in an all-solid-state secondary battery. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] International Publication No. 2017 / 169616 [Patent Document 2] JP 2017-54615 A Summary of the Invention [Problem to be solved by the invention]
[0011] Incidentally, the application field of all-solid-state secondary batteries is expanding rapidly at present, and applications requiring discharge at a large current value are also considered, so that it is required to improve the load characteristics to meet this. In addition, as a charging method for all-solid-state secondary batteries, a method of charging at a constant current until the battery voltage reaches a predetermined value (constant current charging) and then charging at a constant voltage until the current value decreases and reaches a predetermined value (constant voltage charging) is generally used. However, for example, in order to improve the rapid charging characteristics of all-solid-state secondary batteries, it is preferable that the charging capacity during constant current charging is large. Thus, as a means for improving the load characteristics and charging capacity during constant current charging (CC capacity) of all-solid-state secondary batteries, for example, the resistance value of the negative electrode can be reduced, and therefore the development of a technology to achieve this is required.
[0012] As described above, Patent Document 2 claims that the resistance of the negative electrode active material can be reduced by covering the structural defects of the negative electrode active material having a graphite structure with small particulate lithium niobate, but this does not reduce the resistance value of the negative electrode to a level that sufficiently enhances the above-mentioned characteristics of the all-solid-state secondary battery.
[0013] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a negative electrode for an all-solid-state secondary battery having a low resistance value, a method for producing the same, and an all-solid-state secondary battery using the negative electrode. [Means for solving the problem]
[0014] The negative electrode for an all-solid-state secondary battery of the present invention has a molded body of a negative electrode mixture containing a negative electrode material including a negative electrode active material and a solid electrolyte, the negative electrode material contains a carbon material as a negative electrode active material, and has a layer containing an oxide having lithium ion conductivity formed on a surface thereof, the amount of the oxide per 100 parts by mass of the carbon material is 1 part by mass or more, and the solid electrolyte contains a sulfide-based solid electrolyte.
[0015] The negative electrode for an all-solid-state secondary battery of the present invention can be produced by the production method of the present invention, which is characterized by including the following negative electrode material formation step (A) and a step (B) of forming a molded body of a negative electrode mixture using the negative electrode material obtained through the negative electrode material formation step (A) and a sulfide-based solid electrolyte.
[0016] Here, the negative electrode material formation step (A) comprises: (1) a step (i-1) of adhering an oxide having lithium ion conductivity or a material for forming the oxide to the surface of a carbon material; and a step (i-2) of firing the carbon material that has been subjected to the step (i-1) to form a layer containing the oxide on the surface of the carbon material such that the amount of the oxide is 1 part by mass or more per 100 parts by mass of the carbon material; or (2) a step (ii) of kneading a carbon material and an oxide having lithium ion conductivity to form a layer containing the oxide on the surface of the carbon material such that the amount of the oxide is 1 part by mass or more per 100 parts by mass of the carbon material.
[0017] The all-solid-state secondary battery of the present invention comprises a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode, and is characterized in that the negative electrode comprises the negative electrode for an all-solid-state secondary battery of the present invention. Effect of the Invention
[0018] According to the present invention, it is possible to provide a negative electrode for an all-solid-state secondary battery having a low resistance value, a method for producing the same, and an all-solid-state secondary battery using the negative electrode. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a cross-sectional view illustrating a schematic example of an all-solid-state secondary battery of the present invention. [Diagram 2] FIG. 2 is a plan view illustrating another example of the all-solid-state secondary battery of the present invention. [Diagram 3] 2. FIG. 2 is a cross-sectional view taken along line II in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] <Negative electrode for all-solid-state secondary batteries> The negative electrode for an all-solid-state secondary battery of the present invention has a molded body of a negative electrode mixture containing a negative electrode material including a negative electrode active material and a solid electrolyte. The negative electrode material is a carbon material that is a negative electrode active material and has a layer containing an oxide having lithium ion conductivity formed on the surface thereof, and the solid electrolyte is a sulfide-based solid electrolyte.
[0021] Carbon materials used as negative electrode active materials are generally hydrophobic and have low affinity with sulfide-based solid electrolytes. Therefore, in a negative electrode (a molded body of a negative electrode mixture) containing such a material, it is difficult to form a good interface between the two, making it difficult to reduce the resistance value of the negative electrode.
[0022] Therefore, in the present invention, a carbon material having a layer containing an oxide having lithium ion conductivity formed on the surface is used as the negative electrode material. The negative electrode material has a high affinity with the sulfide-based solid electrolyte and can form a good interface. Therefore, the negative electrode for the all-solid-state secondary battery of the present invention has a low resistance value and a high lithium ion acceptance, so that it is possible to increase the CC capacity of the all-solid-state secondary battery using the negative electrode (i.e., the all-solid-state secondary battery of the present invention) and also to improve the load characteristics.
[0023] Examples of negative electrodes for all-solid-state secondary batteries include a molded body (such as a pellet) obtained by molding a negative electrode mixture, and a structure in which a layer (negative electrode mixture layer) made of a molded body of a negative electrode mixture is formed on a current collector.
[0024] Examples of carbon materials constituting the negative electrode material include graphite (natural graphite; artificial graphite obtained by graphitizing easily graphitizable carbons such as pyrolytic carbons, mesophase carbon microbeads, and carbon fibers at 2800°C or higher; etc.), easily graphitizable carbon (soft carbon), difficult to graphitize carbon (hard carbon), pyrolytic carbons, cokes, glassy carbons, fired bodies of organic polymer compounds, mesophase carbon microbeads, carbon fibers, activated carbon, and the like, and one or more of these may be used.
[0025] The oxide constituting the layer formed on the surface of the negative electrode material has lithium ion conductivity, and examples of the oxide include lithium niobium oxide (LiNbO3, etc.), lithium titanium oxide (LiTiO 12 Lithium phosphate oxide (Li3PO4, etc.), lithium boron oxide (Li3BO3, etc.), lithium tungsten oxide (Li4WO5, etc.), lithium aluminum oxide (LiAlO2, etc.), etc. Although Li3PO4 is an oxide-based solid electrolyte, other oxide-based solid electrolytes, such as Li7La3Zr2O 12 , LiTi(PO4)3, LiGe(PO4)3, LiLaTiO3, etc. can also be used as constituent materials for the layer formed on the surface of the negative electrode material.
[0026] The amount of the oxide having lithium ion conductivity in the negative electrode material is 1 part by mass or more, preferably 1.5 parts by mass or more, per 100 parts by mass of the carbon material, from the viewpoint of ensuring a good effect of reducing the resistance value of the negative electrode for an all-solid-state secondary battery. However, if the amount of the oxide is too large, the capacity of the negative electrode active material may be reduced, or the conductivity of the negative electrode mixture in the molded body may be reduced. Therefore, the amount of the oxide having lithium ion conductivity in the negative electrode material is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, per 100 parts by mass of the carbon material.
[0027] The oxide contained in the layer formed on the surface of the negative electrode material is preferably amorphous, since this enhances the effect of enhancing the load characteristics of the CC capacity of the all-solid-state secondary battery. The fact that the oxide is amorphous can be confirmed, for example, by the absence or broadness of a peak representing the crystallization of the oxide when X-ray diffraction (XRD) is performed.
[0028] The negative electrode mixture in the negative electrode for all-solid-state secondary batteries can contain, together with the negative electrode material, other negative electrode active materials commonly used in lithium-ion secondary batteries. However, when using other negative electrode active materials together with the negative electrode material in the negative electrode active material, it is preferable that the proportion of the negative electrode material in all the negative electrode active materials is 60% by mass or more. Note that since the negative electrode mixture in the negative electrode for all-solid-state secondary batteries may not use negative electrode active materials other than the negative electrode material, the preferable upper limit value of the proportion of the negative electrode material in all the negative electrode active materials is 100% by mass.
[0029] The content of all the negative electrode active materials including the negative electrode material in the negative electrode mixture is preferably 30 to 70% by mass.
[0030] Examples of the sulfide-based solid electrolyte in the negative electrode for all-solid-state secondary batteries include particles such as Li2S-P2S5, Li2S-SiS2, Li2S-P2S5-GeS2, and Li2S-B2S3-based glasses. In recent years, LGPS-based materials (Li 10 GeP2S 12 etc.) and argyrodite-based materials [such as Li6PS5Cl, Li 7-x+y PS 6-x Cl x+y (where 0.05 ≦ y ≦ 0.9, -3.0x + 1.8 ≦ y ≦ -3.0x + 5.7), Li 7-a PS 6-a Cl b Br c (where a = b + c, 0 < a ≦ 1.8, 0.1 ≦ b / c ≦ 10.0), etc.] can also be used. Among these, sulfide-based solid electrolytes containing lithium and phosphorus are preferable because of their high lithium ion conductivity, and argyrodite-based materials with particularly high lithium ion conductivity and high chemical stability are more preferable.
[0031] The average particle size of the sulfide-based solid electrolyte is preferably 0.1 μm or more, and more preferably 0.2 μm or more, from the viewpoint of reducing grain boundary resistance, while it is preferably 10 μm or less, and more preferably 5 μm or less, from the viewpoint of forming a sufficient contact interface between the negative electrode material and the solid electrolyte.
[0032] The average particle diameter of the solid electrolyte and the negative electrode active material in this specification is the 50% diameter value (D) in the volume-based integrated fraction when calculating the integral volume from particles with small particle sizes using a particle size distribution measurement device (such as a Microtrac particle size distribution measurement device "HRA9320" manufactured by Nikkiso Co., Ltd.). 50 )
[0033] In the negative electrode for an all-solid-state secondary battery, other solid electrolytes (hydride-based solid electrolytes, oxide-based solid electrolytes, etc.) can be used in addition to the sulfide-based solid electrolyte. However, the proportion of the solid electrolyte other than the sulfide-based solid electrolyte in the total amount of solid electrolyte particles in the negative electrode for an all-solid-state battery is preferably 30 mass% or less. Note that, since the solid electrolyte in the negative electrode for an all-solid-state secondary battery may all be sulfide-based solid electrolytes, the lower limit of the proportion of the solid electrolyte other than the sulfide-based solid electrolyte in the total amount of solid electrolyte is 0 mass%.
[0034] Examples of hydride-based solid electrolytes include LiBH4, solid solutions of LIBH4 and the following alkali metal compounds (for example, those in which the molar ratio of LiBH4 to the alkali metal compound is 1:1 to 20:1), etc. Examples of the alkali metal compounds in the solid solutions include at least one selected from the group consisting of lithium halides (LiI, LiBr, LiF, LiCl, etc.), rubidium halides (RbI, RbBr, RbiF, RbCl, etc.), cesium halides (CsI, CsBr, CsF, CsCl, etc.), lithium amide, rubidium amide, and cesium amide.
[0035] As an oxide-based solid electrolyte, for example, Li7La3Zr2O 12, LiTi(PO4)3, LiGe(PO4)3, LiLaTiO3, etc.
[0036] The average particle size of the solid electrolyte other than the sulfide-based solid electrolyte is preferably approximately the same as the average particle size of the sulfide-based solid electrolyte.
[0037] The content of the solid electrolyte in the negative electrode mixture is preferably 4 to 70 mass %.
[0038] The negative electrode mixture may contain a conductive assistant such as carbon black, graphene, etc., if necessary. When the negative electrode mixture contains a conductive assistant, the content is preferably 1 to 10 mass %.
[0039] The negative electrode mixture may or may not contain a resin binder. Examples of the resin binder include fluororesins such as polyvinylidene fluoride (PVDF). However, since the resin binder acts as a resistance component even in the negative electrode mixture, it is desirable that the amount of the resin binder is as small as possible. Therefore, it is preferable that the negative electrode mixture does not contain a resin binder, or if it does contain one, the content is 0.5 mass% or less. It is more preferable that the content of the resin binder in the negative electrode mixture is 0.3 mass% or less, and even more preferable that it is 0 mass% (i.e., no resin binder is contained).
[0040] When a current collector is used in the negative electrode for an all-solid-state secondary battery, the current collector can be made of copper or nickel foil, punched metal, net, expanded metal, foamed metal; carbon sheet; or the like.
[0041] The negative electrode for an all-solid-state secondary battery can be produced, for example, by a production method including a negative electrode material formation step (A) and a step (B) of forming a molded body of a negative electrode mixture using the negative electrode material obtained through the negative electrode material formation step (A) and a sulfide-based solid electrolyte.
[0042] The negative electrode material formation step (A) includes, for example, a step (i-1) of adhering an oxide having lithium ion conductivity or a material for forming the oxide to the surface of a carbon material, and a step (i-2) of calcining the carbon material that has been subjected to the step (i-1) to form a layer containing the oxide on the surface of the carbon material, thereby obtaining the negative electrode material.
[0043] In step (i-1), the method for attaching an oxide having lithium ion conductivity to the surface of the carbon material may include a method of dissolving or dispersing the oxide in a solvent to prepare a composition and applying it to the surface of the carbon material; a method of dry-mixing the carbon material with the oxide; etc. In step (i-1), the method for attaching a material for forming the oxide to the surface of the carbon material may include a method of dissolving or dispersing the material in a solvent to prepare a composition and applying it to the surface of the carbon material.
[0044] As the solvent for the composition containing the oxide or the composition containing the material for forming the oxide, alcohols such as methanol and ethanol; non-polar aprotic solvents such as hydrocarbon solvents such as hexane, heptane, octane, nonane, decane, decalin, toluene, and xylene; and the like can be used. In addition, when the oxide or the material for forming the oxide contained in the composition is easily reacted with moisture, it is preferable to use a dehydrated solvent (ultra-dehydrated solvent) with a moisture content of 0.001 mass % (10 ppm) or less. On the other hand, when the oxide or the material for forming the oxide is not easily reacted with moisture, water can also be used as the solvent for the composition.
[0045] The method for applying the composition to the carbon material is not particularly limited, and any of various known application methods can be used. The method for dry-mixing the oxide and the carbon material is also not particularly limited, and any of various known mixing methods can be used.
[0046] In step (i-2), the carbon material obtained through step (i-1) is fired to form a layer containing an oxide having lithium ion conductivity on the surface of the carbon material. When a composition containing a material for forming the oxide is applied to the carbon material in step (i-1), the material for forming the oxide is reacted to synthesize the oxide in step (i-2), and a layer containing the oxide is formed.
[0047] The calcination method in step (i-2) is not particularly limited, and various known calcination methods can be used. The calcination temperature in step (B) is preferably a temperature at which the oxide can form a layer in an amorphous state, specifically, preferably 450° C. or lower, and preferably 300° C. or higher. The calcination time in step (B) is preferably 0.5 to 3 hours.
[0048] The negative electrode material formation step (A) may also include, instead of the steps (i-1) and (i-2), a step (ii) of kneading a carbon material with an oxide having lithium ion conductivity to form a layer containing the oxide on the surface of the carbon material.
[0049] In step (ii), the carbon material and the oxide having lithium ion conductivity are kneaded, i.e., mixed while applying shear, to form a layer containing the oxide having lithium ion conductivity on the surface of the carbon material, thereby obtaining a negative electrode material. The method of kneading the carbon material and the oxide is not particularly limited as long as it is a method that can mix the two while applying shear, and various methods using known devices can be adopted.
[0050] Next, in the step (B), the negative electrode material obtained in the negative electrode material formation step (A) and a sulfide-based solid electrolyte are used to form a compact of a negative electrode mixture.
[0051] The negative electrode mixture compact can be formed, for example, by compressing the negative electrode mixture prepared by mixing the negative electrode material, the sulfide-based solid electrolyte, and further, if necessary, a conductive assistant and a binder, by pressure molding, etc. When the negative electrode for the all-solid-state secondary battery is composed only of the negative electrode mixture compact, the negative electrode for the all-solid-state secondary battery can be obtained by this step (B).
[0052] On the other hand, when the negative electrode for an all-solid-state secondary battery has a current collector, the negative electrode for an all-solid-state secondary battery can be obtained by bonding the molded body of the negative electrode mixture obtained in step (B) to the current collector by, for example, pressure bonding.
[0053] The thickness of the negative electrode mixture compact (in the case of a negative electrode having a current collector, the thickness of the positive electrode mixture compact per one side of the current collector; the same applies below) is preferably 200 μm or more from the viewpoint of increasing the capacity of the battery. In general, the load characteristics of a battery are easily improved by making the positive electrode or negative electrode thinner, but according to the present invention, even when the negative electrode mixture compact is as thick as 200 μm or more, the load characteristics can be improved. Therefore, in the present invention, when the thickness of the negative electrode mixture compact is, for example, 200 μm or more, the effect is more remarkable. In addition, the thickness of the negative electrode mixture compact is usually 3000 μm or less.
[0054] <All-solid-state secondary battery> The all-solid-state secondary battery of the present invention has a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode, and the negative electrode is the negative electrode for the all-solid-state secondary battery of the present invention.
[0055] A cross-sectional view showing a schematic example of an all-solid-state secondary battery of the present invention is shown in Fig. 1. In the all-solid-state secondary battery 1 shown in Fig. 1, a positive electrode 10, a negative electrode 20, and a solid electrolyte layer 30 interposed between the positive electrode 10 and the negative electrode 20 are enclosed in an exterior body formed of an exterior can 40, a sealing can 50, and a resin gasket 60 interposed between them.
[0056] The sealing can 50 is fitted into the opening of the outer can 40 via a gasket 60, and the open end of the outer can 40 is tightened inward, whereby the gasket 60 comes into contact with the sealing can 50, sealing the opening of the outer can 40 and forming an airtight structure inside the battery.
[0057] The outer can and the sealing can can be made of stainless steel or the like. The gasket can be made of polypropylene, nylon, or other materials. If heat resistance is required for the battery's intended use, heat-resistant resins with melting points exceeding 240°C, such as fluororesins such as tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), polyphenylene ether (PEE), polysulfone (PSF), polyarylate (PAR), polyethersulfone (PES), polyphenylene sulfide (PPS), and polyetheretherketone (PEEK), can also be used. If the battery is used in an application that requires heat resistance, a glass hermetic seal can be used for the sealing.
[0058] 2 and 3 are drawings that diagrammatically show another example of the all-solid-state secondary battery of the present invention. Fig. 2 is a plan view of the all-solid-state secondary battery, and Fig. 3 is a cross-sectional view taken along line II in Fig. 2.
[0059] The all-solid-state secondary battery 100 shown in Figures 2 and 3 houses an electrode assembly 200 consisting of a positive electrode, a solid electrolyte layer, and a negative electrode of the present invention in a laminate film exterior body 500 consisting of two sheets of metal laminate film, and the laminate film exterior body 500 is sealed at its outer periphery by heat fusing the upper and lower metal laminate films. In Figure 3, in order to avoid complicating the drawing, the layers constituting the laminate film exterior body 500 and the positive electrode, negative electrode, and separator constituting the electrode body are not shown separately.
[0060] The positive electrode of the electrode body 200 is connected to the positive electrode external terminal 300 within the battery 100. Also, although not shown, the negative electrode of the electrode body 200 is also connected to the negative electrode external terminal 400 within the battery 100. And one end sides of the positive electrode external terminal 300 and the negative electrode external terminal 400 are drawn out to the outside of the laminate film exterior body 500 so as to be connectable to external devices and the like.
[0061] (Positive electrode) The positive electrode of the all-solid-state secondary battery has, for example, a molded body of a positive electrode mixture containing a positive electrode active material, a conductive assistant, a solid electrolyte, etc., and examples include a positive electrode composed only of the molded body, and a positive electrode having a structure in which the molded body and a current collector are integrated.
[0062] The positive electrode active material is not particularly limited as long as it is a positive electrode active material used in a conventionally known lithium-ion secondary battery, that is, an active material capable of occluding and releasing Li ions. Specific examples of the positive electrode active material include LiM x Mn 2-x O4 (where M is at least one element selected from the group consisting of Li, B, Mg, Ca, Sr, Ba, Ti, V, Cr, Fe, Co, Ni, Cu, Al, Sn, Sb, In, Nb, Mo, W, Y, Ru, and Rh, and 0.01 ≦ x ≦ 0.5), spinel-type lithium manganese composite oxide represented by Li x Mn (1-y-x) Ni y M z O (2-k) F l (where M is at least one element selected from the group consisting of Co, Mg, Al, B, Ti, V, Cr, Fe, Cu, Zn, Zr, Mo, Sn, Ca, Sr, and W, 0.8 ≦ x ≦ 1.2, 0 < y < 0.5, 0 ≦ z ≦ 0.5, k + l < 1, -0.1 ≦ k ≦ 0.2, 0 ≦ l ≦ 0.1), layered compound represented by LiCo 1-x M x O2 (where M is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, and Ba, and 0 ≦ x ≦ 0.5), lithium cobalt composite oxide represented by LiNi1-x M x Lithium nickel composite oxide represented by LiM02 (wherein M is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Fe, Co, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb and Ba, and 0≦x≦0.5) 1-x N x olivine-type composite oxide represented by Li4Ti5OPO4 (wherein M is at least one element selected from the group consisting of Fe, Mn, and Co, and N is at least one element selected from the group consisting of Al, Mg, Ti, Zr, Ni, Cu, Zn, Ga, Ge, Nb, Mo, Sn, Sb, and Ba, and 0≦x≦0.5); 12 Among these, only one type may be used, or two or more types may be used in combination.
[0063] The average particle size of the positive electrode active material is preferably 1 μm or more, more preferably 2 μm or more, and is preferably 10 μm or less, more preferably 8 μm or less. The positive electrode active material may be either primary particles or secondary particles formed by agglomeration of primary particles. When a positive electrode active material having an average particle size in the above range is used, a large interface with the solid electrolyte can be obtained, and thus the load characteristics of the battery are further improved.
[0064] The positive electrode active material preferably has a reaction suppression layer on its surface for suppressing reaction with the solid electrolyte.
[0065] If the positive electrode active material and the solid electrolyte come into direct contact with each other in the positive electrode mixture compact, the solid electrolyte may oxidize to form a resistance layer, which may reduce the ionic conductivity in the compact. By providing a reaction suppression layer that suppresses the reaction with the solid electrolyte on the surface of the positive electrode active material and preventing direct contact between the positive electrode active material and the solid electrolyte, it is possible to suppress the reduction in the ionic conductivity in the compact due to the oxidation of the solid electrolyte.
[0066] The reaction suppression layer may be made of a material that has ion conductivity and can suppress the reaction between the positive electrode active material and the solid electrolyte. Examples of materials that can form the reaction suppression layer include oxides containing Li and at least one element selected from the group consisting of Nb, P, B, Si, Ge, Ti, and Zr, more specifically, Nb-containing oxides such as LiNbO3, Li3PO4, Li3BO3, Li4SiO4, Li4GeO4, LiTiO3, LiZrO3, and the like. The reaction suppression layer may contain only one of these oxides, or may contain two or more of them, and further, a plurality of these oxides may form a composite compound. Among these oxides, it is preferable to use an Nb-containing oxide, and it is more preferable to use LiNbO3.
[0067] The reaction suppression layer is preferably present on the surface in an amount of 0.1 to 1.0 part by mass per 100 parts by mass of the positive electrode active material, in order to effectively suppress the reaction between the positive electrode active material and the solid electrolyte.
[0068] Methods for forming a reaction suppression layer on the surface of a positive electrode active material include the sol-gel method, the mechanofusion method, the CVD method, the PVD method, and the like.
[0069] The content of the positive electrode active material in the positive electrode mixture is preferably 60 to 95 mass %.
[0070] Examples of the conductive assistant for the positive electrode include carbon materials such as graphite (natural graphite, artificial graphite), graphene, carbon black, carbon nanofiber, carbon nanotube, etc. The content of the conductive assistant in the positive electrode mixture is preferably 1 to 10 mass %.
[0071] The positive electrode solid electrolyte may be one or more of the various sulfide-based solid electrolytes, hydride-based solid electrolytes, and oxide-based solid electrolytes listed above as examples of those usable for the negative electrode. In order to improve the battery characteristics, it is desirable to include a sulfide-based solid electrolyte.
[0072] The content of the solid electrolyte in the positive electrode mixture is preferably 4 to 30 mass %.
[0073] The positive electrode mixture may or may not contain a resin binder. Examples of the resin binder include fluororesins such as polyvinylidene fluoride (PVDF). However, since the resin binder acts as a resistance component in the positive electrode mixture, it is desirable that the amount of the resin binder is as small as possible. Therefore, it is preferable that the positive electrode mixture does not contain a resin binder, or if it does contain one, the content is 0.5 mass% or less. It is more preferable that the content of the resin binder in the positive electrode mixture is 0.3 mass% or less, and even more preferable that it is 0 mass% (i.e., no resin binder is contained).
[0074] When a current collector is used for the positive electrode, the current collector can be made of a metal foil such as aluminum or stainless steel, a punched metal, a net, an expanded metal, a foamed metal, a carbon sheet, or the like.
[0075] The positive electrode mixture compact can be formed, for example, by compressing a positive electrode mixture prepared by mixing a positive electrode active material, a conductive assistant, a solid electrolyte, and further a binder added as necessary, by pressure molding or the like.
[0076] In the case of a positive electrode having a current collector, the positive electrode can be produced by bonding a molded body of the positive electrode mixture formed by the above-mentioned method to the current collector by, for example, pressure bonding.
[0077] The thickness of the positive electrode mixture compact (in the case of a positive electrode having a current collector, the thickness of the positive electrode mixture compact per one side of the current collector; the same applies below) is preferably 200 μm or more from the viewpoint of increasing the capacity of the battery. The thickness of the positive electrode mixture compact is usually 2000 μm or less.
[0078] (Solid electrolyte layer) The solid electrolyte in the solid electrolyte layer may be one or more of the various sulfide-based solid electrolytes, hydride-based solid electrolytes, and oxide-based solid electrolytes exemplified above as those usable for the negative electrode. However, in order to improve the battery characteristics, it is preferable to contain a sulfide-based solid electrolyte, and it is more preferable to contain a sulfide-based solid electrolyte in all of the positive electrode, negative electrode, and solid electrolyte layer.
[0079] The solid electrolyte layer may have a porous body such as a resin nonwoven fabric as a support.
[0080] The solid electrolyte layer can be formed by a method of compressing a solid electrolyte by pressure molding or the like; a method of applying a composition for forming a solid electrolyte layer, which is prepared by dispersing a solid electrolyte in a solvent, onto a substrate, a positive electrode, or a negative electrode, drying the composition, and, if necessary, performing pressure molding such as pressing.
[0081] It is preferable to select a solvent that does not deteriorate the solid electrolyte for use in the composition for forming the solid electrolyte layer. In particular, since sulfide-based solid electrolytes and hydride-based solid electrolytes undergo chemical reactions due to a small amount of water, it is preferable to use a non-polar aprotic solvent represented by a hydrocarbon solvent such as hexane, heptane, octane, nonane, decane, decalin, toluene, or xylene. In particular, it is more preferable to use an ultra-dehydrated solvent with a water content of 0.001 mass% (10 ppm) or less. In addition, fluorine-based solvents such as "Vertrel (registered trademark)" manufactured by Mitsui DuPont Fluorochemicals, "Zeorolla (registered trademark)" manufactured by Nippon Zeon Co., Ltd., and "Novec (registered trademark)" manufactured by Sumitomo 3M Co., Ltd., as well as non-aqueous organic solvents such as dichloromethane and diethyl ether can also be used.
[0082] The thickness of the solid electrolyte layer is preferably 100 to 300 μm.
[0083] (electrode body) The positive electrode and the negative electrode can be used in a battery in the form of a laminated electrode body in which the positive electrode and the negative electrode are laminated with a solid electrolyte layer interposed therebetween, or in the form of a wound electrode body in which this laminated electrode body is wound.
[0084] In forming the electrode body, it is preferable to pressure mold the positive electrode, the negative electrode, and the solid electrolyte layer in a laminated state, from the viewpoint of increasing the mechanical strength of the electrode body.
[0085] (Battery type) The form of the all-solid-state secondary battery may be one having an exterior body composed of an exterior can, a sealing can, and a gasket as shown in FIG. 1, that is, one generally referred to as a coin-type battery or a button-type battery, or one having an exterior body composed of a resin film or a metal-resin laminate film as shown in FIGS. 2 and 3, or one having an exterior body having a metallic, bottomed, tubular (cylindrical or rectangular) exterior can and a sealing structure that seals the opening of the can.
[0086] The all-solid-state secondary battery of the present invention can be used for the same applications as conventionally known secondary batteries, but since it has a solid electrolyte instead of an organic electrolyte, it has excellent heat resistance and can be preferably used for applications in which it is exposed to high temperatures. EXAMPLES
[0087] The present invention will be described in detail below based on examples, but the present invention is not limited to the following examples.
[0088] Example 1 (Formation of solid electrolyte layer) 80 mg of a sulfide-based solid electrolyte (Li6PS5Cl) was placed in a powder molding die with a diameter of 10 mm, and pressure molding was performed using a press machine to form a solid electrolyte layer.
[0089] (Preparation of negative electrode) 0.1 mol of lithium and 0.125 mol of titanium tetraisopropoxide were mixed in 500 mL of dehydrated ethanol to prepare a composition for forming a coating layer. Next, the composition for forming a coating layer was applied to 500 g of graphite for 180 minutes at a speed of 2 g per minute using a coating device using a rolling fluidized bed. The obtained powder was sintered at 400°C for 30 minutes to obtain an oxide having lithium ion conductivity (LiTiO 12 A negative electrode material (1) was obtained, which was made of graphite having a coating layer containing . The amount of oxide in the negative electrode material (1) was 1.91 parts by mass per 100 parts by mass of graphite. It was also confirmed by the above-mentioned method that the oxide constituting the coating layer in the negative electrode material (1) was amorphous.
[0090] The negative electrode material (1), graphene, and the same sulfide-based solid electrolyte as that used for the solid electrolyte layer were mixed in a mass ratio of 45:5:50 and thoroughly kneaded to prepare a negative electrode mixture. Next, 15 mg of the negative electrode mixture was poured onto the solid electrolyte layer in the powder molding die, and pressure molding was performed using a press to form a negative electrode made of a negative electrode mixture compact on the solid electrolyte layer.
[0091] (Formation of laminated electrode body) The counter electrode was made by bonding together Li metal and In metal formed into a cylindrical shape, and the counter electrode was placed on the surface of the solid electrolyte layer in the powder molding die opposite to the negative electrode, and pressure molding was performed using a press to produce a laminated electrode body.
[0092] (Assembly of model cells) Using the laminated electrode body, an all-solid-state battery (model cell) with a planar structure similar to that shown in Fig. 2 was fabricated. A negative electrode current collector foil (SUS foil) and a counter electrode current collector foil (SUS foil) were attached side by side with a certain amount of space between them on the inner surface of the aluminum laminate film constituting the laminated film exterior body. Each of the current collector foils was cut into a shape that had a main body portion facing the negative electrode side surface or the counter electrode side surface of the laminated electrode body, and a portion that protrudes from the main body portion toward the outside of the battery to become the negative electrode external terminal 400 and the counter electrode external terminal 300.
[0093] The laminated electrode body was placed on the negative electrode current collector foil of the laminated film exterior body, and the laminated electrode body was wrapped in the laminated film exterior body so that the counter electrode current collector foil was positioned on the counter electrode of the laminated electrode body. The remaining three sides of the laminated film exterior body were then sealed by heat fusion under vacuum to obtain a model cell.
[0094] Example 2 0.1 mol of lithium and 0.1 mol of niobium pentoxide were mixed in 500 mL of dehydrated ethanol to prepare a composition for forming a coating layer. Next, the composition for forming a coating layer was applied to 500 g of graphite at a speed of 2 g per minute for 184 minutes using a coating device using a rolling fluidized bed. The obtained powder was fired at 400°C to obtain a negative electrode material (2) made of graphite on whose surface a coating layer containing an oxide (LiNbO3) having lithium ion conductivity was formed. The amount of oxide in the negative electrode material (2) was 2.55 parts by mass relative to 100 parts by mass of graphite. It was also confirmed by the above method that the oxide constituting the coating layer in the negative electrode material (2) was amorphous.
[0095] A negative electrode was produced in the same manner as in Example 1 except that the negative electrode material (2) was used instead of the negative electrode material (1), and a model cell was produced in the same manner as in Example 1 except that this negative electrode was used.
[0096] Example 3 A negative electrode material (3) was prepared in the same manner as in Example 2, except that the coating layer-forming composition was applied to the graphite at a rate of 2 g per minute for 132 minutes. The amount of oxide in the negative electrode material (3) was 1.83 parts by mass per 100 parts by mass of graphite. It was also confirmed by the above-mentioned method that the oxide constituting the coating layer in the negative electrode material (3) was amorphous.
[0097] A negative electrode was produced in the same manner as in Example 1 except that the negative electrode material (3) was used instead of the negative electrode material (1), and a model cell was produced in the same manner as in Example 1 except that this negative electrode was used.
[0098] Example 4 A negative electrode material (4) was prepared in the same manner as in Example 2, except that the coating layer-forming composition was applied to the graphite at a rate of 2 g per minute for 72 minutes. The amount of oxide in the negative electrode material (4) was 1 part by mass per 100 parts by mass of graphite. It was also confirmed by the above-mentioned method that the oxide constituting the coating layer in the negative electrode material (4) was amorphous.
[0099] A negative electrode was produced in the same manner as in Example 1 except that the negative electrode material (4) was used instead of the negative electrode material (1), and a model cell was produced in the same manner as in Example 1 except that this negative electrode was used.
[0100] Example 5 20 g of graphite and 1 g of Li3PO4 were thoroughly mixed to obtain a negative electrode material (5) made of graphite with a coating layer containing an oxide (Li3PO4) having lithium ion conductivity formed on the surface. The amount of the oxide in the negative electrode material (5) was 5 parts by mass relative to 100 parts by mass of graphite.
[0101] A negative electrode was produced in the same manner as in Example 1 except that the negative electrode material (5) was used instead of the negative electrode material (1), and a model cell was produced in the same manner as in Example 1 except that this negative electrode was used.
[0102] Example 6 The composition for forming a coating layer was applied onto 300 g of hard carbon at a rate of 4 g per minute for 190 minutes. The obtained powder was sintered at 400° C. for 30 minutes to obtain an oxide having lithium ion conductivity (LiTiO 12 A negative electrode material (6) made of hard carbon having a coating layer containing ) formed on the surface was obtained. The amount of oxide in the negative electrode material (6) was 6.72 parts by mass relative to 100 parts by mass of the hard carbon.
[0103] A negative electrode was produced in the same manner as in Example 1 except that the negative electrode material (6) was used instead of the negative electrode material (1), and a model cell was produced in the same manner as in Example 1 except that this negative electrode was used.
[0104] Comparative Example 1 A negative electrode material (7) was prepared in the same manner as in Example 2, except that the coating layer-forming composition was applied to the graphite at a rate of 2 g per minute for 36 minutes. The amount of oxide in the negative electrode material (7) was 0.5 parts by mass relative to 100 parts by mass of graphite. It was also confirmed by the above-mentioned method that the oxide constituting the coating layer in the negative electrode material (7) was amorphous.
[0105] A negative electrode was produced in the same manner as in Example 1 except that the negative electrode material (7) was used instead of the negative electrode material (1), and a model cell was produced in the same manner as in Example 1 except that this negative electrode was used.
[0106] Comparative Example 2 A negative electrode was prepared in the same manner as in Example 1, except that graphite not having a coating layer formed on its surface was used instead of the negative electrode material (1). A model cell was prepared in the same manner as in Example 1, except that this negative electrode was used.
[0107] Comparative Example 3 A negative electrode was prepared in the same manner as in Example 1, except that hard carbon not having a coating layer formed on its surface was used instead of the negative electrode material (6). A model cell was prepared in the same manner as in Example 1, except that this negative electrode was used.
[0108] The model cells having the negative electrodes of the Examples and Comparative Examples were subjected to the following evaluations.
[0109] <CC Capacity Evaluation> For each model cell, at a temperature of 23°C under pressure (1 t / cm 2 ), constant current charging was performed at a current value of 0.05C until the voltage reached 0.62V, followed by constant voltage charging at a voltage of 0.62V until the current value reached 0.01C. Subsequently, discharging was carried out at a current value of 0.05C until the voltage reached 1.88V. This series of steps was repeated twice. The capacity during the second constant current charging and the capacity during the second discharging (initial capacity) were determined. Then, the value obtained by dividing the capacity during the second constant current charging of each model cell by the initial capacity was expressed as a percentage to evaluate the CC capacity.
[0110] <DC Resistance (DCR) Measurement> For each model cell after the initial capacity measurement, at a temperature of 23°C under pressure (1 t / cm 2 ), constant current charging and constant voltage charging were performed under the same conditions as during the initial capacity measurement. Subsequently, discharging was carried out at a current value of 0.1C until the state of charge (SOC) reached 50%, and then a 1-hour pause was made. For each model cell thereafter, after performing a 10-second pulse discharge at a current value of 0.1C, the voltage was measured. The voltage obtained by subtracting the voltage rise attributed to the solid electrolyte layer and the counter electrode from the voltage difference before and after the pulse discharge was used to calculate the DCR.
[0111] It can be said that the lower the internal resistance of the negative electrode used in the model cell with a smaller DCR obtained by this method, the better the load characteristics, and it is possible to construct an all-solid-state secondary battery with a large CC capacity.
[0112] The above evaluation results are shown in Table 1 together with the composition of the negative electrode material.
[0113]
Table 1
[0114] The model cells prepared in Examples 1 to 6 used negative electrodes made of a molded body of a negative electrode mixture containing a negative electrode material having a layer containing an appropriate amount of oxide having lithium ion conductivity on the surface of a carbon material and a sulfide-based solid electrolyte, and had low DCR. Therefore, by using these negative electrodes, the load characteristics and CC capacity of the all-solid-state secondary battery can be improved.
[0115] In contrast, the model cell of Comparative Example 1 used a negative electrode containing a negative electrode material with a small amount of oxide on its surface, and the model cells of Comparative Examples 2 and 3 used negative electrodes containing a carbon material that did not have a layer containing oxide on its surface, but the DCR of these cells was higher than that of the Examples. [Explanation of symbols]
[0116] 1,100 All-solid-state secondary battery 10 positive electrode 20 negative electrode 30 Solid electrolyte layer 40 Outer can 50 sealed cans 60 Gasket 200 Electrode body 300 Positive external terminal 400 Negative external terminal 500 Laminated film exterior
Claims
1. The battery has a molded body of a negative electrode mixture containing a negative electrode material including a negative electrode active material and a solid electrolyte, the negative electrode material contains a carbon material as a negative electrode active material, and a layer containing an oxide having lithium ion conductivity is formed on a surface of the negative electrode material; the amount of the oxide is 1 part by mass or more relative to 100 parts by mass of the carbon material, A negative electrode for an all-solid-state secondary battery, comprising a sulfide-based solid electrolyte as the solid electrolyte.
2. 2. The negative electrode for an all-solid-state secondary battery according to claim 1, wherein the oxide comprises lithium niobium oxide, lithium titanium oxide or lithium phosphate.
3. A method for producing a negative electrode for an all-solid-state secondary battery having a molded body of a negative electrode mixture containing a negative electrode material including a negative electrode active material and a solid electrolyte, comprising: The following negative electrode material forming step (A), and a step (B) of forming a compact of a negative electrode mixture using the negative electrode material obtained through the negative electrode material formation step (A) and a sulfide-based solid electrolyte. The negative electrode material forming step (A) comprises: The method includes a step (i-1) of attaching an oxide having lithium ion conductivity or a material for forming the oxide to a surface of a carbon material, and a step (i-2) of firing the carbon material that has been subjected to the step (i-1) to form a layer containing the oxide on the surface of the carbon material such that the amount of the oxide is 1 part by mass or more relative to 100 parts by mass of the carbon material, or The method includes a step (ii) of kneading a carbon material with an oxide having lithium ion conductivity to form a layer containing the oxide on a surface of the carbon material such that the amount of the oxide is 1 part by mass or more per 100 parts by mass of the carbon material.
4. The method for producing a negative electrode for an all-solid-state secondary battery according to claim 3, wherein in the step (i-2), the firing is performed at a temperature of 450° C. or less.
5. 3. An all-solid-state secondary battery comprising: a positive electrode; a negative electrode; and a solid electrolyte layer interposed between the positive electrode and the negative electrode, the negative electrode being the negative electrode for an all-solid-state secondary battery according to claim 1.
Citation Information
Patent Citations
All solid secondary battery
JP2015118815A
Negative electrode active material and all-solid secondary battery
JP2016207570A
Coated negative-electrode active material
JP2017054615A
Negative electrode active material for nonaqueous electrolyte secondary batteries
WO2017169616A1
Cited By
Electrode, solid electrolyte mixture, and battery
WO2026163766A1